Impacto na eficiência energética em sistemas de irrigação sem manutenção: estudo de caso - Breda, Júlio César da Silva (Universidade Federal de São Carlos, 2025)
The pursuit of energy efficiency is essential in agriculture, as electricity represents one of the sector’s main inputs. This study analyzes the impact of the lack of maintenance on the energy efficiency of irrigation systems using water pumping. The research is based on a case study conducted on a farm, where data were collected on energy consumption, hydraulic performance, and system losses. The methodology involved measurements of current, voltage, and pressure, as well as calculations using the Hazen-Williams equation and the pump performance curve. The results showed that the lack of maintenance leads to a significant increase in energy consumption and a reduction in system efficiency. After a partial intervention, an improvement in pump performance and a decrease in operational costs were observed. It is concluded that preventive maintenance is essential to ensure energy efficiency and reduce waste in the agricultural sector.
Impact on energy efficiency in irrigation systems without maintenance: a case study
Keywords: Eficiência energética; Irrigação; Manutenção preventiva; Bombeamento hídrico; Consumo de energia; ENGENHARIAS::ENGENHARIA ELETRICA::CIRCUITOS ELETRICOS, MAGNETICOS E ELETRONICOS